Multimodal Imaging Characteristics and Functional Test Findings in a Case of Acute Macular Neuroretinopathy Accompanied by Behçet Disease. (17th November 2021) - Batıoğlu, Figen; Yanık, Özge; Demirel, Sibel; Özmert, Emin
ABSTRACT: Purpose : To report a case of acute macular neuroretinopathy (AMN) in Behçet Disease. Case : A 23-year-old male presented with a complaint for central scotoma in his right eye. He had been diagnosed with Behçet Disease 3 years ago. Best-corrected visual acuity (BCVA) was 20/20. Anterior chamber and fundus examinations were unremarkable. Optical coherence tomography revealed a paracentral area of outer nuclear layer thinning. Infrared reflectance showed a well-defined, circular, hyporeflective area. Optical coherence tomography angiography revealed an area of capillary dropout in deep retinal capillary plexus corresponding to that hyporeflective lesion. Microperimetry test showed decreased macular sensitivity on the lesion area and the loss of the macular integrity. In multifocal electroretinogram, diminished amplitudes of the central cone responses were detected nasal to fixation. Conclusion : Behçet disease is a cause of occlusive retinal vasculitis. Accompanied retinal microvascular disease may be a possible risk factor of AMN suggesting ischemic etiopathogenesis for AMN.